Fall Prevention Decision Making of Acute Care Registered Nurses. (September 2020) - Fehlberg, Elizabeth A.; Cook, Christa L.; Bjarnadottir, Ragnhildur I.; McDaniel, Anna M.; Shorr, Ronald I.; Lucero, Robert J.
Abstract : OBJECTIVE: The aim of this study was to examine acute care registered nurses' (RNs') fall prevention decision-making. BACKGROUND: The RN decision-making process related to fall prevention needs to be investigated to ensure that hospital policies align with nursing workflow and support nursing judgment. METHODS: Qualitative semistructured interviews based on the Critical Decision Method were conducted with RNs about their planning and decision making during their last 12-hour shift worked. RESULTS: Data saturation was achieved with 12 RNs. Nine themes emerged related to the RN decision-making process and included hospital-level (eg, fear of discipline), unit-level (eg, value of bed alarm technology), and nurse-level (eg, professional judgment) factors that could influence fall prevention. CONCLUSIONS: Nursing administrators should consider a multilevel approach to fall prevention policies that includes promoting a practice environment that embraces self-reporting adverse events without fear of shame or being reprimanded, evaluating unit-level practice and technology acceptance and usability, and supporting autonomous nursing practice. Abstract : Supplemental digital content is available in the text.